2021
DOI: 10.1088/1741-2552/ab7c8e
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of primary somatosensory cortex of the hand area using a high-density electrocorticography grid for closed-loop brain computer interface

Abstract: Objective. The ideal modality for generating sensation in sensorimotor brain computer interfaces (BCI) has not been determined. Here we report the feasibility of using a high-density ‘mini’-electrocorticography (mECoG) grid in a somatosensory BCI system. Approach. Thirteen subjects with intractable epilepsy underwent standard clinical implantation of subdural electrodes for the purpose of seizure localization. An additional high-density mECoG grid was placed (Adtech, 8 by 8, 1.2 mm exposed, 3 mm center-to-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Such high degree of anatomical overlap among the evoked percepts restricts the amount of sensory information that can be conveyed. Meanwhile, with their the larger size and inter-contact spacing, HD-ECoG electrodes elicit more diffuse sensory percepts (14, 16, 53). Additionally, with the capability to record or modulate the neural activity of neurons that lie within 1-2 mm below the cortical surface (54), these electrodes provide access to only the gyral surfaces of the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high degree of anatomical overlap among the evoked percepts restricts the amount of sensory information that can be conveyed. Meanwhile, with their the larger size and inter-contact spacing, HD-ECoG electrodes elicit more diffuse sensory percepts (14, 16, 53). Additionally, with the capability to record or modulate the neural activity of neurons that lie within 1-2 mm below the cortical surface (54), these electrodes provide access to only the gyral surfaces of the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tactile percepts in the hand have been evoked in humans through intracortical microstimulation using microelectrode arrays (11)(12)(13) or cortical surface stimulation using electrocorticography (ECoG) grids (14)(15)(16) in the primary somatosensory cortex (S1). Although such artificial sensory feedback help improve the user performance with a BCI system (17), focal percepts in fingertips that would be critical for dexterous manipulations have been difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, eliciting positive reports of sensory percepts instead of negative (numbness) reports or inactivating motor functions transiently 5 may be difficult, 38 and prior studies have demonstrated low specificity and variability of cortical stimulation, 39 including overlapping activations of multiple fingers due to direct cortical stimulation. 40,41 Recent studies with high density (3mm inter-electrode distance) ECoG-based stimulation have demonstrated higher degree of individual finger specificity, 42,43 although it is unclear if this approach could delineate fingertip versus more proximal finger/palm regions. Researchers have found a correlation between cortical stimulation, perception of sensation, and high gamma activity, pointing to overlap of the OFM and ECS methods.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tactile percepts in the hand have been evoked in humans through intracortical microstimulation using microelectrode arrays [10][11][12] or cortical surface stimulation using electrocorticography (ECoG) grids [13][14][15] in the primary somatosensory cortex (S1), specifically cortical area 1. Although such artificial sensory feedback helps improve the user performance with a BCI system [16], focal percepts in fingertips that would be critical for dexterous manipulations as those mentioned above [17] have been difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%